Ignition Promotion Effect of Spark Discharge on Ignition in Low Compression Ratio Direct Injection Diesel Engines Fueled with FAME Having High Cetane Number - KONDO, Chihiro; YAMANE, Koji; KUMAZAWA, Naoto; KAWASAKI, Kiyoshi (Nihon Kikai Gakkai rombunshuu. B hen, 2012)
The aim of this study is to demonstrate the combustion system that the ignition is promoted by the spark discharge into pre-mixture formed during long ignition delay time due to low compression ratio direct injection diesel engines. In this paper, an experimental study has been conducted to investigate the potential of effect of spark discharge on combustion process by changing spark timing, injection timing, equivalence ratio and an amount of fuel. As a fuel, lauric methyl ester (LaME) is used that is one of the fatty acid methyl ester (FAME) and has characteristics of relatively high volatility and high ignition quality. From the result, it was found that in the case of volumetric efficiency 34% spark-induced ignition (S.I.I.)_combustion is observed, in the S.I.I. condition, the ignition delay time advanced for about 5 degree CA, and the ignition timing is controlled by spark timing within 5 degree CA. Furthermore, the applicability of starting performance is also discussed which is one of the major problems in low compression ratio diesel engines due to lower temperature at the end of the compression stroke, compared with the high compression ratio diesel engines.